Non-Covalent Assembly Method that Simultaneously Endows a Liposome Surface with Targeting Ligands, Protective PEG Chains, and Deep-Red Fluorescence Reporter Groups - Shaw, Scott K. (Chemistry, 2017)
A new self-assembly method is used to rapidly functionalize the surface of liposomes without perturbing the membrane integrity or causing leakage of the aqueous contents. The key molecule is a cholesterol-squaraine-PEG conjugate with three important structural elements: a cholesterol membrane anchor, a fluorescent squaraine docking station that allows rapid and high-affinity macrocycle threading, and a long PEG-2000 chain to provide steric shielding of the decorated liposome. The two-step method involves spontaneous insertion of the conjugate into the outer leaflet of pre-formed liposomes followed by squaraine threading with a tetralactam macrocycle that has appended targeting ligands. A macrocycle with six carboxylates permitted immobilization of intact fluorescent liposomes on the surface of cationic polymer beads, whereas a macrocycle with six zinc(II)-dipicolylamine units enabled selective targeting of anionic membranes, including agglutination of bacteria in the presence of human cells.